2001
DOI: 10.1021/cm0011716
|View full text |Cite
|
Sign up to set email alerts
|

Sol−Gel Processing of Au Nanoparticles in Bulk 10 B2O3−90 SiO2Glass

Abstract: Bulk borosilicate glasses were prepared by the sol-gel process and doped with gold nanoparticles. First, a sol of the host glass (with nominal molar composition of 10% B 2 O 3 -90% SiO 2 ) was prepared, and then gold was introduced into the sol by means of a solution of a Au 3+ complex. The resulting gels were dried at 60 °C and then heated in air at various temperatures up to 600 °C to nucleate the gold particles and sinter the glass matrix. Various gold ligands were tested, and thiourea was found to be the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Solid monolith glasses with the optical properties determined by the composition of these bimetallic particles can be obtained upon drying a silica gel containing the nanoparticles [13]. The production of coloured glasses through the sol-gel synthesis of nanoparticles has been considered as an alternative method for glass production with some advantages over the traditional process, among them are the low processing temperatures, and a better control over the optical properties of the glass material [18][19][20][21]. Au-Ag alloy nanoparticles were also synthesized in solid state inside a glassy silica film matrix through the interlayer diffusion of the Ag and Au contained in different sol-gel coating layers during the thermal treatment [22].…”
Section: Introductionmentioning
confidence: 99%
“…Solid monolith glasses with the optical properties determined by the composition of these bimetallic particles can be obtained upon drying a silica gel containing the nanoparticles [13]. The production of coloured glasses through the sol-gel synthesis of nanoparticles has been considered as an alternative method for glass production with some advantages over the traditional process, among them are the low processing temperatures, and a better control over the optical properties of the glass material [18][19][20][21]. Au-Ag alloy nanoparticles were also synthesized in solid state inside a glassy silica film matrix through the interlayer diffusion of the Ag and Au contained in different sol-gel coating layers during the thermal treatment [22].…”
Section: Introductionmentioning
confidence: 99%
“…S. Tamil Selvan et al (2002) prepared sol-gel-derived gold nanoclusters in silica glass for potential photonic applications. M. Epifani et al (2001) prepared bulk borosilicate glasses (with nominal molar composition of 10 % B 2 O 3 -90 % SiO 2 ) doped with gold nanoparticles by sol-gel process and found that Au particles have two patterns of existence form: face-centered cubic Au and orthorhombic Au 3 Si.…”
Section: The Common Hybrid Borosilicate Glass Metal and Metal Oxide Nmentioning
confidence: 99%
“…Among the different processing techniques [3][4][5][6][7] used in an attempt to synthesize nanoparticles of uniform size, shape, and depth distribution, ion implantation provides an attractive method of fabricating metal nanoparticles in solids due in part to the spatial controllability. However, subsequent annealing after the implantation promotes Ostwald ripening and associated particle growth, thus creating a wide size distribution of particles.…”
Section: Introductionmentioning
confidence: 99%